2006
DOI: 10.1080/10550490601003664
|View full text |Cite
|
Sign up to set email alerts
|

Early Therapeutic Alliance as a Predictor of Treatment Outcome for Adolescent Cannabis Users in Outpatient Treatment

Abstract: The association of early alliance to treatment attendance and longitudinal outcomes were examined in 356 adolescents participating in a randomized clinical trial targeting cannabis use. Both patient and therapist views of alliance were examined, and outcomes were evaluated over 12 months after numerous other sources of variance were controlled. Patient-rated alliance predicted a reduction in cannabis use at three and six months and a reduction in substancerelated problem behaviors at six months. Therapistrated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
56
1
7

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(71 citation statements)
references
References 46 publications
7
56
1
7
Order By: Relevance
“…Similar patterns have been found with adolescent samples. Higher problem recognition (one element of motivation) is associated with stronger counselor relationships (Garner, Godley, & Funk, 2008), and counselor relationships promote during-treatment reductions in substance use (Crits-Christoph et al, 2011) as well as improved outcomes following treatment (Diamond et al, 2006; Garnick et al, 2012). Thus, the critical elements of the recovery process likely involve sufficient retention, motivation for treatment, therapeutic relationships, and psychological functioning.…”
Section: Introductionmentioning
confidence: 99%
“…Similar patterns have been found with adolescent samples. Higher problem recognition (one element of motivation) is associated with stronger counselor relationships (Garner, Godley, & Funk, 2008), and counselor relationships promote during-treatment reductions in substance use (Crits-Christoph et al, 2011) as well as improved outcomes following treatment (Diamond et al, 2006; Garnick et al, 2012). Thus, the critical elements of the recovery process likely involve sufficient retention, motivation for treatment, therapeutic relationships, and psychological functioning.…”
Section: Introductionmentioning
confidence: 99%
“…It is well established in the general treatment literature that the therapeutic relationship is related to positive outcomes (1) and this holds true when treating substance use disorders (2)(3)(4)(5)(6). Although various therapeutic models may have equivalent effects (7), it is common in the treatment of substance use disorders for providers to incorporate Twelve-Step Program (TSP) concepts and principles into their approach (8), and several studies have found an association between TSP participation and positive outcomes (9)(10)(11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…L'alliance est un élément influençant positivement la rétention en traitement ou les changements obtenus autant chez les adolescents toxicomanes (Diamond & al., 2006 ;Tetzlaff & al., 2005) que chez ceux présentant des symptômes dépressifs ayant fait une tentative de suicide (Karver & al., 2008). Le Guide de bonnes pratiques à l'intention des intervenants des centres de santé et de services sociaux (Lane, Archambault, CollinsPoulette & Camirand, 2010) indique des pistes intéressantes pour la création de l'alliance thérapeutique avec un individu en crise suicidaire, celles-ci pourraient aussi être appliquées aux jeunes toxicomanes qui présentent des comportements suicidaires.…”
Section: Discussionunclassified